GERAKAN PUNGUAN MARGA BATAK PARNA DALAM PEMENANGAN GUNTUR SIMARMATA PADA PEMILIHAN CALON LEGISLATIF DI KABUPATEN ROKAN HULU TAHUN 2024 - Simanjuntak, Jetro Sumando; ,, Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Local elections often become complex arenas where various social and cultural actors play crucial roles in shaping political directions. In Rokan Hulu Regency, kinship-based organizations or clans have an undeniable influence in political contests, including in securing victories for candidates. This study analyzes the role of Punguan Marga Batak Parna (Punguan Parna) in supporting the election of Guntur Simarmata in Rokan Hulu's local election. The main focus of this research is to examine how Punguan Parna, as a kinship-based organization, implements resource mobilization strategies to achieve its political objectives. This study employs the resource mobilization theory as an analytical framework to understand the process of gathering and utilizing various resources, including human resources (members), financial, informational, and networking assets owned by Punguan Parna. Using a qualitative approach with a case study method, the research finds that Punguan Parna effectively mobilized its members through kinship ties, clan solidarity, and intensive communication. Financial resources were collected through member contributions and voluntary donations, while information was systematically disseminated through regular meetings and personal networks. Furthermore, extensive social networks, both internal and external, were utilized to broaden support and influence. The findings reveal that Guntur Simarmata's success was strongly influenced by Punguan Parna's capacity to strategically orchestrate and direct its available resources. This study provides information into how social organizations with strong identity foundations can play significant roles in local political arenas through well-planned resource mobilization mechanisms. Key Words : Punguan Marga Batak Parna, Resource Mobilization, General Elections, Guntur Simarmata, Rokan Hulu.